TESTING OF STRATIFIED CLUSTER SAMPLING TECHNIQUE TO PRODUCE UNBIASED ESTIMATOR FOR PARAMETER OF POPULATION - Muhammad Yunus (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2018)
This research is done based on the importance testing of sampling technique before the real survey is done. The aim of this research is to test stratified cluster sampling technique in producing unbiased estimator of population. Based on theory, stratified cluster sampling technique is able to produce unbiased estimator. The reserch method used survey technique where the subjects are the whole the twelveth grade ofSenior High School in lubuklinggau and Musi Rawas. The calculation sample shows that the real number of population is 54,45 % whereas the result of sample is 55,5 %with sampling error 0,0464,therefore the samples have estimated parameter of population accuratly.